Reducing Underage and Young Adult Drinking: How to Address Critical Drinking Problems During This Developmental Period. - Windle, Michael; Zucker, Robert A. (Alcohol Research & Health, 2010)
Forty years ago, when the National Institute on Alcohol Abuse and Alcoholism (NIAAA) was founded, alcoholism was considered an adult disease driven principally by physiological determinants. As NIAAA expanded its research portfolio, new data and insights were obtained that led to an increased focus on underage and young adult drinking. Fostered by interdisciplinary research, etiologic models were developed that recognized the multiplicity of relevant genetic and environmental influences. This shift in conceptualizing alcohol use disorders also was based on findings from large-scale, national studies indicating that late adolescence and early young adulthood were peak periods for the development of alcohol dependence and that early initiation of alcohol use (i.e., before age 15) was associated with a fourfold increase in the probability of subsequently developing alcohol dependence. In recent years, developmental studies and models of the initiation, escalation, and adverse consequences of underage and early young adult drinking have helped us to understand how alcohol use may influence, and be influenced by, developmental transitions or turning points. Major risk and protective factors are being identified and integrated into screening, prevention, and treatment programs to optimize interventions designed to reduce drinking problems among adolescents and young adults. In addition, regulatory policies, such as the minimum drinking age and zero-tolerance laws, are being implemented and evaluated for their impact on public health. INSET: NIAAA'S UNDERAGE DRINKING RESEARCH INITIATIVE.